Interlanguage And Interlanguage Continuum - Tofan Dwi Hardjanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1995)
The aim of this article is to examine the basic concepts underlying the notion of interlanguage and its related aspects, that is interlanguage continuum and tossilisation. It will be obvious in the course of the discussion that attention will be focused on the interlanguage continuum, the ways in which second language learners progress along it, and why at any one stage in this continuuma learner may fossi lise.